Nonparametric comparison of regression curves - an empirical process approach - Dette, Holger; Neumeyer, Natalie (Universitätsbibliothek Dortmund, 2000)
We propose a new test for the comparison of two regression curves, which is based on a difference of two marked empirical processes based on residuals. The large sample behaviour of the corresponding statistic is studied to provide a full nonparametric comparison of regression curves. In contrast to most procedures suggested in the literature the new procedure is applicable in the case of different design points and heteroscedasticity. Moreover, it is demonstrated that the proposed test detects continuous alternatives converging to the null at a rate N
Keywords: 310